COLLEGE ACCOUNTING TESTING PROGRAM. - Wood, Ben D.; Traxler, Arthur E.; Nissley, Warren W. (The Accounting Review, 1948)
In 1943; the American Institute of Accountants appointed a committee on selection of Personnel to investigate procedures for selecting and guiding into public accounting well qualified young people and to develop a program of selection. After preliminary investigation, the Committee secured the cooperation of several specialists in evaluation to serve in an advisory capacity and to handle the technical aspects of the project. The Educational Records Bureau, a non-profit making organization of schools arid colleges, which had many years of experience in handling a test service program, was chosen as the operating agency for the project. From the outset, the Committee took a broad-gage view of both the technical and social aspects of the total problem. They recognized from the outset that the personnel in the profession at any given time was the result of a long process ranging from original recruitment of students through selection at the point of employment, and elimination, retention, and promotion after employment.